Methodological principles of analysis and selection of investment projects for reconstruction taking into account their technical condition - Malykhin , Mykhailo; Kuzmin, Timur; Hyria, Valentyn (Ways to Improve Construction Efficiency, 2025)
The article is devoted to the substantiation of the methodological principles of analysis and selection of investment projects for the reconstruction of buildings that have been damaged or destroyed due to prolonged operation or external influences. The focus of the study is the formation of an integrated approach to assessing the technical condition of objects, determining the level of their degradation and predicting the needs for emergency restoration work. The significance of surveys, non-destructive diagnostic methods and monitoring systems as basic tools for recording the actual state of structures, their deformations, structural violations and reduction in bearing capacity is revealed. The classification of damage and destruction is carried out with the determination of their impact on the operational properties and safety of the object. Particular attention is paid to the role of digitalization and BIM modeling as key factors in improving the quality and consistency of design solutions in reconstruction processes. It is shown that the creation of digital models and information databases allows integrating survey results, monitoring data, engineering calculations and organizational and technological parameters into a single information environment. This provides a much more accurate determination of the scope of reconstruction work, a reliable assessment of the technical condition and justified investment design. The capabilities of BIM modeling for automated detection of spatial collisions, optimization of technological solutions and increased management efficiency in a multi-project environment are emphasized. The proposed methodological approach includes phased diagnostics of the technical condition, risk analysis, identification of critical destructions, construction of cost models and formation of a multi-criteria base for assessing the effectiveness of reconstruction projects. It has been proven that the integration of technical, economic and organizational information contributes to making informed decisions, increases the reliability of investment calculations and minimizes the likelihood of errors in the design and implementation of reconstruction works.